2014
DOI: 10.1038/nnano.2014.254
|View full text |Cite
|
Sign up to set email alerts
|

Towards non-invasive diagnostic imaging of early-stage Alzheimer's disease

Abstract: One way to image the molecular pathology in Alzheimer’s disease (AD) is by positron emission tomography using probes that target amyloid fibrils. However, these fibrils are not closely linked to the development of the disease. It is now thought that early stage biomarkers that instigate memory loss comprise of Aβ oligomers (AβOs). Here we report a sensitive molecular magnetic resonance imaging (MRI) contrast probe that is specific for AβOs. We attach oligomer-specific antibodies onto magnetic nanostructures an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
120
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(127 citation statements)
references
References 44 publications
3
120
0
4
Order By: Relevance
“…Using PET for diagnosis of AD, Viola et al [41] found that Aβ oligomers are responsible for memory loss in patients with AD. The oligomer-specific antibodies, binding to Aβ oligomers, are induced into brain tissues and cells.…”
Section: Clinical Neurophysiological Diagnosis Of Admentioning
confidence: 99%
“…Using PET for diagnosis of AD, Viola et al [41] found that Aβ oligomers are responsible for memory loss in patients with AD. The oligomer-specific antibodies, binding to Aβ oligomers, are induced into brain tissues and cells.…”
Section: Clinical Neurophysiological Diagnosis Of Admentioning
confidence: 99%
“…Structural magnetic resonance imaging (sMRI), provides high accuracy when diagnosing patients with AD vs. controls, especially in advanced stages of the disease [3,4]. However, early diagnostic accuracy for identifying AD and prognostic value for patients diagnosed with early AD using sMRI remains problematic [5].…”
Section: Introductionmentioning
confidence: 99%
“…This antibody-conjugated MNP quickly reached the oligomers, owing to active targeting and has shown clear intense MRI signals in the hippocampus region of brain in contrast to wild-type control mouse which showed absence of signals. This substantiated its use as a probe in AD pathology [50].…”
Section: Theranostic Approach Of Mnps For Neurodegenerative Diseasementioning
confidence: 71%